Suitability of Informatics curriculum tools for 21st-century digital literacy - Rakha Akhyara (Himpunan Pengembang Kurikulum Indonesia, 2026)
The implementation of the Kurikulum Merdeka at the senior high school level requires contextual, flexible, and student-centered learning, including in the Informatics subject. One important competency to develop is digital literacy, which includes the ability to access, understand, evaluate, and ethically and responsibly use information from various digital sources. This study aims to evaluate the alignment between the Informatics subject curriculum and 21st-century digital literacy needs. The research method uses a descriptive qualitative approach, through curriculum document analysis, interviews with teachers, and a review of the digital learning facilities and resources available in the school environment. The study's results indicate that the curriculum includes learning objectives and outcomes designed to strengthen digital literacy. However, its implementation in the field still faces various challenges, such as limited technological devices, low digital competence among teachers, and insufficient integration of project-based or collaborative learning. Additionally, not all students demonstrate independence in learning or the ability to evaluate digital information critically. Therefore, there is a need to strengthen policies, enhance educators' capacities, and provide infrastructure support as prerequisites for creating an adaptive and relevant Informatics learning ecosystem that meets the demands of the digital age. Abstrak Pelaksanaan Kurikulum Merdeka pada tingkat sekolah menengah atas memerlukan pembelajaran yang kontekstual, fleksibel, dan berpusat pada murid, termasuk dalam mata pelajaran Informatika. Salah satu kompetensi penting yang harus dikembangkan adalah literasi digital, yang mencakup kemampuan untuk mengakses, memahami, mengevaluasi, dan memanfaatkan informasi dari berbagai sumber digital secara etis dan bertanggung jawab. Penelitian ini bertujuan untuk mengevaluasi kesesuaian antara kurikulum mata pelajaran Informatika dengan kebutuhan literasi digital abad ke-21. Metode penelitian menggunakan pendekatan kualitatif deskriptif, melalui analisis dokumen kurikulum, wawancara dengan guru, dan tinjauan fasilitas dan sumber daya pembelajaran digital yang tersedia di lingkungan sekolah. Hasil penelitian menunjukkan bahwa secara substansial, kurikulum mencakup tujuan dan hasil belajar yang bertujuan untuk memperkuat literasi digital. Namun, implementasi di lapangan masih menghadapi berbagai tantangan, seperti keterbatasan perangkat teknologi, rendahnya kompetensi digital di kalangan guru, dan kurangnya integrasi berbasis proyek atau kolaboratif. Selain itu, tidak semua murid menunjukkan kemandirian dalam belajar dan kemampuan untuk mengevaluasi informasi digital secara kritis. Oleh karena itu, diperlukan penguatan kebijakan, peningkatan kapasitas pendidik, dan dukungan infrastruktur sebagai prasyarat untuk menciptakan ekosistem pembelajaran Informatika yang adaptif dan relevan yang memenuhi tuntutan era digital. Kata Kunci: keterampilan abad ke-21; kurikulum Informatika; Kurikulum Merdeka; literasi digital